Financial Planning Bagi Siswa Madrasah Aliyah di Gresik Sebagai Upaya Mendorong Investasi - Vilantika, Elok (Jurnal Pengabdian Manajemen, 2025)
People with sound financial planning abilities can steer clear of excessive debt, make better financial judgments, and get ready for a more secure financial future. Students in high school still have a poor level of awareness regarding the significance of financial planning. Through outreach, this community service project seeks to educate youngsters about the value of sound money management from a young age. Since financial planning promotes investment, it aids in kids' education. Through engaging lectures and lively debates, the outreach strategy pushed students to establish financial objectives and recognize the value of investing and saving. The activity's outcomes showed that students' comprehension and desire to learn more about investments had grown. This demonstrates that financial planning and investment are appropriate approaches to increasing students' financial interest and awareness.